Disability in the Palestinian Territories : Assessing Situation and Services for People with Disabilities - World Bank (World Bank, Washington, DC, 2016)
This assessment originated from the dialogue on reforming the Cash Transfer Program (CTP) managed by the Ministry of Social Affairs (MOSA) to increase monetary support for people with disabilities (PWD). According to the beneficiaries, the current benefit payment is not sufficient to address the special needs of a household with a member with disability. In response to the demand of the beneficiaries, the MOSA considered additional compensation for vulnerable households including PWD; an analysis was conducted to weight the costs and benefits of modifying the targeting formula to accommodate additional compensation for PWD. The results did not support increasing the monetary compensation because the costs of adjustment were expected to outweigh the benefits and do so at the expense of larger number of poor beneficiaries. Furthermore, global evidence suggests that cash transfers are not necessarily the sole or right instrument to address the needs of PWD in an adequate manner. Rather, meeting the needs requires a holistic approach with greater focus on providing services complemented by temporary cash benefits. Also, compensating only by cash is not sustainable.